HUBUNGAN KONDISI SOSIAL EKONOMI ORANG TUA TERHADAP MOTIVASI LULUSAN SMK MELANJUTKAN PENDIDIKAN TINGGI - Julkat Nia Laoli; Eka Septianti Laoli; Wahyutra Adilman Telaumbanua; Arianto Lahagu (Jurnal Ilmiah Bina Edukasi, 2025)
The powerlessness of the community, especially parents, in improving their children's education is caused by economic problems, one of which is the economic problem. The research method used is a quantitative research method. Based on data analysis, the results obtained are a strong relationship between the socio-economic conditions of parents and the motivation of students to continue higher education. This result is proven by the Partial test (T Test) with the results of the T count value obtained of 3.274. It is concluded that T count (3.274) > T table (2.042) with the results of H0 rejected H1 accepted. Supported by the significant results of the Partial T Test of 0.003 with the criteria if sig > α (0.05), then H0 is accepted H1 is rejected otherwise sig < α (0.05), then H0 is rejected H1 is accepted. Thus, the sig value of 0.003 < 0.05 has the status of H0 rejected and H1 accepted. Indicates that the socio-economic conditions of parents have a significant relationship with the motivation of students to continue higher education.